Professional Identity in Training: Trajectory of students of the Physical Education course (Research, Society and Development, 2023)
This article aimed to investigate the construction of the professional identity of students enrolled in the Physical Education course at the Federal University of Pará (UFPA), specifically on the university campus of Castanhal/PA. To achieve this objective, qualitative research was carried out through semi-structured interviews with students. The results revealed that participants had diverse experiences with the area, which included sports and exposure to a variety of activities. Furthermore, it was evidenced that the students' greatest experiences occurred during Elementary and High School, which may have influenced their often mistaken conceptions about the subject before entering Undergraduate Studies. These findings highlight the importance of considering students' primary experiences when planning pedagogical approaches to teaching the subject. Thus, based on the results, it is a fact that the initial training of these future professionals must critically address previous conceptions and provide opportunities for in-depth reflection on the teacher's professional identity.